Reliability of Simple Space Truss Structure - Toga Sitompul, Sang; Pariatmono, Pariatmono (ASTONJADRO, 2022)
Structural analysis has been widely applied in civil engineering. This analysis based on probability theory. Structural analysis was carried out to calculate the probability of failure and reliability of the structure. There are many cases of construction failure caused by uncertain environmental and human activities, including improper load in the external design process. In the process of designing a structure in Indonesia, complicated analysis is rarely carried out because of the complexity and impracticality of the analysis. Engineers and developers need to understand the behavior of the space truss structure and procedures in structural reliability analysis, Therefore it is necessary to simplify the structure in the analysis of the structure. This paper has carried out a structural reliability analysis using simple space truss modeling to understand its structural behavior and the principles of structural analysis under indeterministic load with simplified methods to make it more practical. A comparison of struktural analysis was carried out on 3 methods of structural analysis, manual calculation, ETABS v9.7.4, and MStower V6.20.1.11. The results of the three methods have the same value so that the structural analysis using MStower is reliable. In the loading approach, the load that is developed into a population of possible loads that can occur. Monte Carlo simulation is used by generate a sample of the load population that can represent the number of possible loads so as to reduce the number of analyzes. Random value generation methods were compared to get a more effective and practical method. The failure criteria are determined to obtain the limit state function of the structure so that the probability of failure and the reliability of the structure can be calculated. In this study, the limit state function was obtained in compression member with a 67% probability of failure and 33% reliability of the structure.